MATHEMATICAL MODELING OF OIL HEATING PROCESS - Toyirov Muhriddin Zoir o’g’li (Journal of new century innovations, 2023)
Abstract. This article is based on a mathematical model based on fuzzy logic in oil production. The obtained analysis was performed. The implementation of this task can be achieved by mathematical modeling of the oil heating process in the oil refining system. Mathematical modeling involves the calculation of a number of values and indicators